The Effect of Lying in Prone Position on Blood Pressure and Heart Rate with and without Massage - Narges Meftahi; Soha Bervis; Shohreh Taghizadeh; Farahnaz Ghafarinejad (Shiraz University of Medical Sciences, 2014)
Background: At the present time, massage has become a popular therapy employed in complementary medicine. There is evidence showing that back massage might have many positive psychological effects, possibly due to having many autonomic nervous system afferent inputs. One of the frequent positions during massage is prone position. However, there has been limited research investigating the effect of back massage in the prone position on blood pressure (BP) and heart rate (HR). The present study planned to investigate the changes of blood pressure and heart rate after back massage in prone position. Methods: Sixty-one healthy women were divided into two groups. Group one lay prone and was given a 15-minute massage while group two just lay prone for 15 minutes. Immediately prior to and after interventions, systolic and diastolic blood pressure and heart rate were measured in both groups. To assess within group differences, paired t-test was used. Independent t-test was also used to assess between group differences. Results: The results showed that systolic blood pressure decreased significantly after massage and also in the group only lying prone (P<0.05), with no significant difference between groups (P>0.05). Changes of diastolic blood pressure and heart rate were not significant in either group. Conclusion: Massage and lying prone both can cause a decrease in systolic blood pressure. Massage was not seen to be more efficient than lying prone.